2011
DOI: 10.1002/ijc.25765
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and residential exposure to electromagnetic fields and risk of brain tumors in adults: A case–control study in Gironde, France

Abstract: The etiology of brain tumors remains largely unknown. Among potential risk factors, exposure to electromagnetic fields is suspected. We analyzed the relationship between residential and occupational exposure to electromagnetic field and brain tumors in adults. A case-control study was carried out in southwestern France between May 1999 and April 2001. A total of 221 central nervous system tumors (105 gliomas, 67 meningiomas, 33 neurinomas and 16 others) and 442 individually ageand sex-matched controls selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 44 publications
0
27
0
4
Order By: Relevance
“…Also to be remembered, MRI use does not only differ between geographical regions and time periods as assessed in the present study, but presumably also varies with health complaints, among socioeconomic groups, genders, age groups, and not at least depends on MRI availability. Thus, differences in MRI use may act as a possible confounder in comparative studies concerning potential carcinogenic exposures, such as the use of mobile telephones, 4,10 exposure to other electromagnetic fields, 1,8 or air pollution. 13 The main strength of the present population-based study is the quality and completeness of the registrybased data.…”
Section: Discussionmentioning
confidence: 99%
“…Also to be remembered, MRI use does not only differ between geographical regions and time periods as assessed in the present study, but presumably also varies with health complaints, among socioeconomic groups, genders, age groups, and not at least depends on MRI availability. Thus, differences in MRI use may act as a possible confounder in comparative studies concerning potential carcinogenic exposures, such as the use of mobile telephones, 4,10 exposure to other electromagnetic fields, 1,8 or air pollution. 13 The main strength of the present population-based study is the quality and completeness of the registrybased data.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory and epidemiological studies have pointed out that EMF could cause disorder in cardiovascular and central nervous system, and also play roles in the occurrence of cancer (Baldi et al, 2011;Jeong et al, 2005;Johansen, 2000). Sharifian, Gharavi, Pasalar, & Aminian (2009) reported that extremely low frequency magnetic field (ELF-MF) affects the human antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…The topic is under public scrutiny as it is a considerable environmental issue, with nearly all of civilized world being exposed to some forms of EMF from either natural or artificial sources. A study in France showed that occupational and residential exposure to EMF might play a role in the occurrence of meningioma (Baldi et al 2011). Another study in Sweden assessed the potential dangers of exposure to EMF, and suggested a possible relationship between parental occupational exposure to EMF and the incidence of leukemia (Feychting et al 2000).…”
Section: Introductionmentioning
confidence: 99%